The outlaw queen [large type] - Richards, Dusty; Doty, Dennis (Thorndike Press, a part of Gale, a Cengage Company, 2025)
Mary Ann Cates owns a successful farm with her husband. While not wealthy by any means, life has been good, even with Charlie away most of the time buying and selling cattle. That all changes, though, when he ends up dead in a shootout with the law. Everything he'd ever told her had been a lie. 'Cattle buyer' really meant 'bank robber'. Shattered and alone, the lovely widow is shunned by the citizens of her Kansas hometown and branded the 'Outlaw Queen'. Rath Macon is a rancher working the Chisholm Trail. It's a good life ... just not good enough for his wife. After returning from the drive, he finds she's spent all their money and run away with another man. As the bank auctions off everything he's worked so hard for, Rath saddles up and rides out of Texas to look for a fresh start with nothing but three horses and the clothes on his back. That's how fate steps in and lassos Rath and Mary Ann. When their eyes lock, embers ignite. But they've both danced to life's fickle fiddle before. Can they rebuild trust on life's treacherous trail?